PERAN PENDIDIKAN ISLAM GUNA MENCIPTAKAN GENERASI QUR’ANI UNTUK BERPARTISIPASI DALAM KEHIDUPAN BERBANGSA DAN BERNEGARA - Suprima, Suprima; Noor, Hafidz; Budiyanti, Nurti; Parhan, Muhamad (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2021)
As a majority Muslim population in the country of Indonesia, of course, it takes an existence from the Muslim community itself to be able to participate in the life of the nation and state. To participate, it requires a procedure or rules that must be studied first, one of which is through Islamic education. Islamic education has a goal so that the next generation can learn, understand, and apply the Islamic values contained therein. Through Islamic education, it is hoped that later the Muslim population can participate in the life of the nation and state in a polite, polite manner, and not to damage the unity and integrity of the Indonesian nation. Through this research, the author wants to find out how the Muslim population can place a strategic position in the life of the nation and state through the principles in the Qur'an and Hadith